m6A mRNA demethylase FTO regulates melanoma tumorigenicity and response to anti-PD-1 blockade - Seungwon Yang (Nature Portfolio, 2019)
FTO is an m6A demethylase. Here, the authors show that FTO promotes melanoma tumorigenicity and contributes to resistance to anti-PD1 blockade, while FTO inhibition sensitizes melanoma to anti-PD1 blockade.